THE ISSUE OF MORALITY IN THE PHILOSOPHICAL HERITAGE OF IBN SINA AND ITS IMPORTANCE IN THE EDUCATION OF YOUNG PEOPLE - Raupova Ra’no Sohibovna (Bright Mind Publishing, 2025)
This article analyzes the issue of morality in the philosophical heritage of Ibn Sina and its importance in the education of young people. In his works, which are considered the spiritual heritage of Ibn Sina, the problems of morality, philosophy, spirituality, and enlightenment are analyzed on a scientific basis and covered based on sources.
Keywords: Philosophy, human, self, knowledge, ethics, youth education, moral values, spirituality, enlightenment.